2010
DOI: 10.1007/s10695-010-9459-7
|View full text |Cite
|
Sign up to set email alerts
|

Iron exposure modifies acetylcholinesterase activity in zebrafish (Danio rerio) tissues: distinct susceptibility of tissues to iron overload

Abstract: Iron is one the most abundant metals on the earth being essential for living organisms even though its free form can be toxic. The overload of this metal may be related with some disorders, like Alzheimer and Parkinson diseases, and hemochromatosis in the liver. The aim of the present study was to evaluate the effects of iron on acetylcholinesterase (AChE) activity in brain and liver of zebrafish and to investigate the possible correlation with the iron content in these tissues. Different corresponding concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 45 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…The inhibition under the effect of Pb could be caused by binding the metal to the functional groups of proteins like imidazole, sulfhydryl, and carboxyl (23). There was emergence of catalytic activity loss in functional groups (24). It showed a significant inhibition of AChE in the brain and muscle tissues following sublethal administration of cadmium (Cd) to zebrafish (25).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition under the effect of Pb could be caused by binding the metal to the functional groups of proteins like imidazole, sulfhydryl, and carboxyl (23). There was emergence of catalytic activity loss in functional groups (24). It showed a significant inhibition of AChE in the brain and muscle tissues following sublethal administration of cadmium (Cd) to zebrafish (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, plasma cholinesterase activity may vary as a function of exposure to other toxic compounds, depending on the exposure period. When studying the effect of exposure to iron on acetylcholinesterase (AChE) enzyme activity in fish brains and livers, Sant' Anna et al (2011) observed an increase of this enzyme 24 hours after exposure. Carvalho et al (2017) obtained similar results when they evaluated the activity of this enzyme in the brain of tadpoles after 48 hours of exposure to different types of heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…It was determined that AChE activity is inhibited by metals like lead and zinc in the brain tissue of Danio rerio (Richetti et al, 2011).It is thought that the inhibition of AChE activity under the effect of lead is caused by binding of metals to the functional groups of proteins like imidazole, sulfhydryl and carboxyl (Najimi et al, 1997). Catalytic activity loss emerges because of this kind of changes in functional groups (Sant'Anna et al, 2011).…”
Section: Discussionmentioning
confidence: 99%